"You're a disgrace to the uniform!" Lev Protiv's challenge to the police in Moscow streets and on YouTube. Issue 6 (2nd November 2022) - Favarel-Garrigues, Gilles
ABSTRACT: Lev Protiv presents itself as a "social project" intertwining civic involvement, moral policing, and entertaining YouTube content. Promoting a healthy lifestyle and claiming to defend innocent youth, Moscow vigilantes have patrolled public spaces since 2014 in search of people consuming alcohol or smoking, for the purpose of enforcing the law. However, their targets are not only drunkards and youth subculture, but also police who are reluctant to implement the law. Financially supported by the government for two years in 2014 and 2015, and earning money thanks to its YouTube channel, why is Lev Protiv's vigilante activity, openly challenging state authority, tolerated in an authoritarian regime? Based on analysis of raid videos and ethnographic observation, this paper shows that Lev Protiv has imposed a particular form of police oversight from below, forcing law enforcement officers to act as vigilante auxiliaries, partially in line with the governmental management of civil society.